Pengaruh Durasi Penggunaan Media Sosial terhadap Kesehatan Mental Remaja di Desa Kertosono - Raden Mochammad Ilman Indana Fajri Ardikusuma; Bagus Setiawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The rapid development of social media in rural areas, such as Kertosono Village, has increased the duration of use of platforms such as TikTok and Instagram among teenagers to an average of 4.2 hours per day. This condition raises concerns regarding the negative impact on mental health, coupled with low digital literacy and lack of education from the surrounding environment. This study aims to determine the significant influence and large contribution of the duration of social media use to the mental health of adolescents in Kertosono Village. Using a quantitative approach with an associative research type, data were collected from 54 respondents aged 12–18 years through the GHQ-12 questionnaire and analyzed using simple linear regression. The results showed a significant influence between the duration of social media use and adolescent mental health, with a contribution of 45.7% to their psychological condition. These findings indicate the need for interventions in the form of increasing digital literacy and education about the healthy use of social media, especially in rural areas that are experiencing accelerated digitalization.